BREASTFEEDING AS PROTECTION AGAINST CHILD OBESITY: A LITERATURE REVIEW - Gularte, Mariana (2021)
Among the most prevalent morbidities of the 21st century is obesity, which is one of the main topics addressed in the scientific community and with an impact on public health. Due to the significant increase of obese adults and children, the scientific community seeks to detect either protective or predisposing factors for obesity. This review article aims to understand the existence of an association between childhood overweight and obesity and not breastfeeding for an adequate time through epidemiological evidence. To verify this relationship, we used articles found on the following databases: Scielo, Medline, National Center for Biotechnology Information, and the EBSCOhost and Google Scholar platforms published after 2015. Among the analyzed literature - cross-sectional studies, cohort, case-control and randomized experimental trials - it was observed that eight of the eleven studies found a positive association between breastfeeding and reduction in the risk of childhood obesity; two studies did not find a significant association, and only one showed a negative relationship between these factors.